Root colonization by arbuscular mycorrhizal fungi (AMF) in various age classes of revegetation post-coal mine - Mohammad Agus Salim; SRI WILARSO BUDI R.; LULUK SETYANINGSIH; ISKANDAR ISKANDAR; IMAM WAHYUDI; HIFZIL KIRMI (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Salim MA, Budi RSW, Setyaningsih L, Iskandar, Wahyudi I, Kirmi H. 2020. Root colonization by arbuscular mycorrhizal fungi (AMF) in various age classes of revegetation post-coal mine. Biodiversitas 21: 5013-5022. This study aims to evaluate the status of colonization of the roots of the host plant in various age classes of revegetation of post-coal mining land associated with AMF spores populations and soil fertility. The study was conducted in the post-mining revegetation land at PT. Berau Coal, East Kalimantan. Isolation of the spores was carried out using the wet-sieving and centrifugation method, while the colonization of the roots was carried out by the root coloring technique. Revegetation activities have been able to increase the content of some nutrients in the soil. The AMF population shows tendency an increase along with the increasing revegetation age classes. Eight-year revegetation age classes have the highest average number of spores. Plant species and understorey have shown the existence of AMF colonization with different values for each species. AMF root colonization has a negative relationship with the number of spores in the soil. The C-organic, N-total, CEC Ca, Mg and Fe contents have a positive correlation with AMF root colonization, while available P, total P, K, and Al have a negative correlation with AMF root colonization. Mg was significantly correlated (r = 0.861) to AMF root colonization.